Periodic health checkups reduce the risk of hospitalization in patients with type 2 diabetes - Hamasaki, Hidetaka; Yanai, Hidekatsu (Frontiers in Clinical Diabetes and Healthcare, 2023)
Introduction: Periodic health checkup (PHC) is a unique system in Japan, which is useful for early detection of lifestyle-related diseases and cardiovascular disease (CVD). This study aims to investigate the association of conducting PHC with the risk of hospitalization in patients with type 2 diabetes mellitus (T2DM). Methods: We conducted a retrospective cohort study from April 2013 to December 2015. We included participants’ information such as history of CVD, lifestyle, and whether PHC was conducted in addition to regular medical examinations. The difference in clinical data between patients with and without PHC was examined. Furthermore, Cox regression analysis for investigating the independent association between PHC and hospitalization was also performed. Results: In this study 1,256 patients were selected and followed up for 2.35 ± 0.73 years. In the PHC group, body mass index (BMI), waist circumference (WC), the number of patients who had history of CVD, and the number of hospitalizations were lower than those in the non-PHC group. Furthermore, the PHC group had a significant association with a less risk of getting hospitalised (hazard ratio = 0.825; 95% confidence interval, 0.684 to 0.997; p = 0.046) in the Cox model. Conclusion: This study revealed that conducting PHC has a role in minimising the risk of hospitalization in patients with T2DM. We have also discussed the effectiveness of PHC to promote health outcomes and reduce health care costs in patients with T2DM.